2009
DOI: 10.1111/j.1472-765x.2009.02644.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofMycobacterium aviumssp.paratuberculosisin milk by UV treatment

Abstract: Aims:  To determine the effect of UV radiation on the viability of two strains of Mycobacterium avium ssp. paratuberculosis (Map) inoculated into milk. Methods and Results:  Mycobacterium avium ssp. paratuberculosis in a ultra heat treated milk matrix was subjected to increasing doses of UV‐C radiation from 0 to 1836 mJ ml−1 using a pilot‐scale UV reactor (20 l capacity). Survival of Map was monitored by culture on Herrold’s egg yolk medium, Middlebrook 7H10 medium and the FASTPlaqueTB™ phage assay. Difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…A number of studies regarding the use of ultrasound to inactivate microorganisms in milk accompanied by heat (Bermúdez-Aguirre & Barbosa-Cánovas, 2008;Bermúdez-Aguirre et al, 2009;Cabeza et al, 2010;Chouliara, Georgogianni, Kanellopoulou, & Kontominas, 2010;Noci, Walkling-Ribeiro, Cronin, Morgan, & Lyng, 2008) and pressure (Lee, Zhou, Liang, Feng, & Martin, 2009;Villamiel & Jong, 2000) and UV-C light (Altic, Rowe, & Grant, 2007;Donaghy et al, 2009;Krishnamurthy, Demirci, & Irudayaraj, 2007) have been conducted. Researches indicated that the use of UV radiation alone did not represent an alternative to current pasteurization applications for a large reduction in viable bacteria counts in milk.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies regarding the use of ultrasound to inactivate microorganisms in milk accompanied by heat (Bermúdez-Aguirre & Barbosa-Cánovas, 2008;Bermúdez-Aguirre et al, 2009;Cabeza et al, 2010;Chouliara, Georgogianni, Kanellopoulou, & Kontominas, 2010;Noci, Walkling-Ribeiro, Cronin, Morgan, & Lyng, 2008) and pressure (Lee, Zhou, Liang, Feng, & Martin, 2009;Villamiel & Jong, 2000) and UV-C light (Altic, Rowe, & Grant, 2007;Donaghy et al, 2009;Krishnamurthy, Demirci, & Irudayaraj, 2007) have been conducted. Researches indicated that the use of UV radiation alone did not represent an alternative to current pasteurization applications for a large reduction in viable bacteria counts in milk.…”
Section: Introductionmentioning
confidence: 99%
“…paratuberculosis possesses several characteristics that may account for its environmental fitness under extreme conditions. The thick, lipid-rich cell wall is responsible for its extreme tolerance to heat (17,20,41,42) and resistance to desiccation (9,10) and UV radiation (43). The thermal tolerance of M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining resistance concluded that although numbers of M. avium subsp. paratuberculosis were reduced by pasteurization (72°C), chlorination of water (2 ppm) (44), and exposure to 24 min of UV radiation in milk (43), viable cells could still be isolated after these treatments. Turbulent-flow pasteurization has also been shown to significantly reduce but not eradicate M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
“…However the rate of inactivation measured by both culture and Phage Amplification Assay were identical, so that even though a proportion of the population was detected, these cells were inactivated in the same rate as the rest of the culture. Similarly Donaghy et al (2009) used the Phage Amplification assay to monitor UV inactivation of MAP using a novel pilot-scale UV treatment for milk. Again there was a discrepancy between the cfu and pfu values obtained, and some evidence of large differences in the infectivity of different strains of MAP, but despite this the inactivation curves obtained were identical and the pfu data was available within 24 h whereas the culture results required up to 18 weeks for growth of the colonies.…”
Section: Enumeration Assaysmentioning
confidence: 99%